2021
DOI: 10.1083/jcb.202004086
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinases USP20/33 promote the biogenesis of tail-anchored membrane proteins

Abstract: Numerous proteins that have hydrophobic transmembrane domains (TMDs) traverse the cytosol and posttranslationally insert into cellular membranes. It is unclear how these hydrophobic membrane proteins evade recognition by the cytosolic protein quality control (PQC), which typically recognizes exposed hydrophobicity in misfolded proteins and marks them for proteasomal degradation by adding ubiquitin chains. Here, we find that tail-anchored (TA) proteins, a vital class of membrane proteins, are recognized by cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 55 publications
3
19
0
Order By: Relevance
“…However, it still remains to be determined how much of a contribution these proteins make to endogenous TA protein targeting within the native cellular environment. Interestingly, human cells lacking SGTA or BAG6 are viable, and TA protein targeting to the ER can still be accomplished in the absence of these factors ( Culver and Mariappan, 2021 ). It is possible, therefore, for capture by the pretargeting complex to be bypassed, and perhaps in this context, other chaperones, analogous to those characterized in yeast, contribute to the initial protection of nascent TA proteins before their association with TRC40.…”
Section: Capture Of Nascent Ta Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it still remains to be determined how much of a contribution these proteins make to endogenous TA protein targeting within the native cellular environment. Interestingly, human cells lacking SGTA or BAG6 are viable, and TA protein targeting to the ER can still be accomplished in the absence of these factors ( Culver and Mariappan, 2021 ). It is possible, therefore, for capture by the pretargeting complex to be bypassed, and perhaps in this context, other chaperones, analogous to those characterized in yeast, contribute to the initial protection of nascent TA proteins before their association with TRC40.…”
Section: Capture Of Nascent Ta Proteinsmentioning
confidence: 99%
“…2 ; Guna et al, 2018 ). The existence of alternative, partially redundant, targeting pathways, supported by the nonlethality of yeast, plant, and human GET pretargeting factor knockouts ( Stefanovic and Hegde, 2007 ; Schuldiner et al, 2008 ; Jonikas et al, 2009 ; Srivastava et al, 2017 ; Xing et al, 2017 ; Culver and Mariappan, 2021 ), likely helps ensure high-fidelity and robust targeting of TA proteins in vivo.…”
Section: Capture Of Nascent Ta Proteinsmentioning
confidence: 99%
“…They consist of an N-terminal MSP domain, a central coiled-coil domain and a C-terminal transmembrane domain ( Figure 1 ) [ 18 ]. As tail-anchored proteins, VAPA/B insert post-translationally into ER membranes [ 28 , 29 ]. VAPC is an alternatively spliced variant of VAPB containing the first 70 amino acids of its MSP domain and an additional unrelated 29 amino acids.…”
Section: The Family Of Vamp-associated Proteins (Vaps) and Vap-related Receptorsmentioning
confidence: 99%
“…BAG6 triages nascent TA proteins in either an insertion competent fraction or destined for proteasomal degradation ( Leznicki and High, 2012 ; Shao et al, 2017 ). Recent work has now demonstrated that polyubiquitinated TA proteins can circumvent recognition by BAG6 and still be inserted via the (mammalian) TRC40 pathway and subsequent deubiquitination ( Culver and Mariappan, 2021 ).…”
Section: Anchoring In the Er Membranementioning
confidence: 99%